The Use of Wordwall Media in Increasing Motivation and Learning Outcomes of Islamic Cultural History (SKI) in Class V MIN 20 Aceh Besar - Saputra, Rifki; Suyanta, Sri; Ariani, Safrina (Teunuleh Publisher, 2026)
This study aims to describe the use of Wordwall media in the subject of Islamic Cultural History, find out the activities of teachers and students, and analyze the increase in motivation and learning outcomes of students in class V of MIN 20 Aceh Besar after the application of the media. The research method used is Kemmis and McTaggart model Class Action Research (PTK) which is carried out in two cycles. The subject of the study is a student of class V MIN 20 Aceh Besar for the 2024/2025 school year. Data collection techniques are carried out through observation, interviews, questionnaires, documentation, and learning outcome tests. The data obtained was analyzed by qualitative and quantitative descriptive analysis techniques, through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the use of Wordwall media can increase student motivation and learning outcomes in SKI subjects. The increase can be seen from the activities of teachers and students who are increasingly active in each cycle, the student learning motivation score that has increased significantly, and the completeness of learning outcomes that have increased from cycle I to cycle II. Thus, Wordwall media has proven to be effective as an interactive learning medium that is able to create a fun learning atmosphere, increase student participation, and improve SKI learning outcomes in class V MIN 20 Aceh Besar.